Body mass index curves for Italian preterm infants are comparable with American curves for infants born before 34 weeks of gestational age. - Paviotti, Giulia; Monasta, Lorenzo; Ronfani, Luca; Montico, Marcella; Copertino, Marco; De Cunto, Angela; Demarini, Sergio (Acta Paediatr, 2016)
AIM: Body mass index (BMI)-for-age curves have been developed in the USA, but not compared with other populations. This study created gender-specific intrauterine BMI-for-age curves for Italian preterm infants and compared them with the USA version. METHODS: Data on 92 262 newborn infants, born at 26-42 weeks of gestational age in the north-eastern Italian region of Friuli Venezia Giulia between 2005 and 2013, were analysed to create gender-specific BMI-for-age curves. Gender-specific and age-specific BMI Z scores for Italian infants were calculated using the parameters of the USA growth curves and the World Health Organization charts. RESULTS: Gender-specific BMI-for-age at birth curves were developed for premature Italian infants from 26 gestational weeks. The comparison with the USA charts showed no significant difference in BMI percentiles in Italian infants born at ≤33 gestational weeks, but infants born at ≥34 gestational weeks had a significantly higher BMI than the USA population, by 0.2 standard deviations. CONCLUSION: We developed the first European BMI-for-age at birth curves for premature infants. According to our findings, the Italian curves were comparable to the USA curves for the subgroup of infants born at ≤33 gestational weeks, but not ≥34 gestational weeks.